Marine Paleoproductivity From the Last Glacial Maximum to the Holocene in the Southwestern Atlantic: A Coccolithophore Assemblage and Geochemical Proxy Perspective - Pedrão, Guilherme A.; Hirama, Marcus V.; Tomazella, Mariana O.; Albuquerque, Ana Luiza S.; Chiessi, Cristiano M.; Costa, Karen B.; Toledo, Felipe A. L. (Frontiers in Earth Science, 2022)
In this study, we associated the variations in coccolithophore assemblages with the variability in major elements (Fe, Ca, and Ti) from the continental slope of the western South Atlantic by investigating two marine sediment cores (GL-824 and GL-1109) to reconstruct paleoceanographic and paleoproductivity changes from the Last Glacial Maximum to the present. Terrigenous-supply proxies (Fe/Ca and Ti/Ca) showed a very similar pattern compared with the fine-fraction sediments – higher values throughout the Last Glacial Maximum (LGM) and lower values during the Holocene. The dominant species in the coccolithophore assemblages were Emiliania huxleyi, Gephyrocapsa spp., and Florisphaera profunda, with these species together representing between 82 and 99% of the total assemblage. Additionally, we used three other subordinate species (Umbellosphaera ssp., Rhabdosphaera spp., and Syracosphaera spp.) for paleoproductivity reconstruction. The estimates of primary production using F. profunda and Gephyrocapsa spp. exhibited a similar trend, with higher productivity values during the LGM. Paleoproductivity decreased toward the Late Holocene. Analyzing these results, we observed that the oscillation of relative sea level was the process that controlled paleoproductivity, primarily by changing the position of the main flow of the Brazil Current (BC). During periods of high sea level (low Fe/Ca and Ti/Ca), the BC transported warm and oligotrophic water to the upper slope, preventing any nutrient transport from deeper layers or coastal water. In contrast, during low sea-level periods (high Fe/Ca and Ti/Ca), the offshore displacement of the BC allowed the presence of coastal water (more nutrient-rich than tropical water) and the erosion of the exposed shelf that along with a more enhanced fluvial input provided more nutrients to the photic zone, thus enhancing primary productivity.